Breeding bio insecurity how U.S. biodefense is exporting fear, globalizing risk, and making us all less secure - Klotz, Lynn C. (University of Chicago Press, 2009)
This book argues that the conditions of research in bioweapons and biosecurity pose a greater risk to health and security of Americans than do bioterrorist attacks, but that this risk can be countered and defeated with greater efforts against infectious diseases and greater international oversight and transparency.